PARADIGMA IJTIHAD DALAM HUKUM ISLAM; KRITIK ATAS EPISTEMOLOGI BERFI KIR KAUM KONTEMPORER - Fadhlurrahman Fadhlurrahman; Yusuf Hanafiah (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2020)
The paradigm in determining Islamic law is very important. Because the scheme is a determinant of quality products. The problems of this era are very diverse. Requires a new spirit in ijtihad. Sometimes religious experts are still fixated on classical methodology in solving religious problems. So that various problems that arise can not be solved. This article uses the library research method to explore the fresh ijtihad paradigm in depth from contemporary thinkers. The results of this study are fresh ijtihad to be very important in answering current issues. The paradigm; firstly, there is a relationship between texts (text) and Interpretation of texts, secondly, Humanity's Dignity and Dignity, thirdly, Islam and Modern Science, fourthly, Ijtihad with Contemporary Science, fifthly, Women's Jurisprudence (Fiqh al-Nisa 'al-Mu'asir ), sixth, Inter-cultural and Inter-faith Dialogue (al-Hiwar; al-Ta'ayus al-Silmy), seventh, Jurisprudence and Social Da'wah, eighth, Universal Jurisprudence and Da'wah, ninth, Jurisprudence and Da'wah Citizenship. Applying the 8 paradigms above must indeed be disintegrated-interconnected so that the basis of religion is maintained and able to answer current problems.